Trends in mortality from acute myocardial infarction among urban and rural residents aged 15 - 79 years in China from 2006 to 2020: an age-period-cohort analysis - Ke LIU; Dongfu QIAN (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo study the trends in mortality from acute myocardial infarction (AMI) among urban and rural residents aged 15 - 79 years in China from 2006 to 2020, and to provide a reference for the development of AMI prevention and control strategies. MethodsData on AMI mortality for urban and rural residents aged 15 - 79 years in China from 2006 to 2020 were collected from the 2007 - 2012 China Health Statistics Yearbook, the 2013 - 2017 China Health and Family Planning Statistics Yearbook, and the 2018 - 2021 China Health Statistics Yearbook. Age-standardized mortality rates for AMI were calculated using the population composition of the 2020 Census. The Joinpoint regression model was used to analyze AMI mortality trends, and the age-period-cohort (APC) model was used to analyze the effects of age, period, and birth cohort on AMI mortality. ResultsFrom 2006 to 2020, the crude AMI mortality rate (1/100 000) increased for all residents (43.93 to 138.94), urban residents (25.53 to 60.29), and rural residents (18.40 to 78.65); the age-standardized mortality rate (1/100 000) also increased for all residents (48.54 to 91.95), urban residents (22.67 to 30.60), and rural residents (25.87 to 61.35), with average annual percentage changes (AAPC) of 8.94%, 3.44%, and 5.49%, respectively (all P < 0.05). The APC model analysis showed different effects of age, period, and birth cohort on AMI mortality trends in the total population and in subgroups as follows: (1) the age effects were lowest in the total, urban, and rural populations aged 15 - 19 years, with effect values (95% confidence interval [95%CI]) of - 2.477 (- 3.413 - 0.894), - 2.532 (- 3.741 - 0.901), and - 2.413 (- 3.362 - 0. 790); the age effect increased continuously with increasing age and was highest in the total, urban, and rural populations aged 75 - 79 years, with effect values (95%CI) of 2.433 (1.867 - 2.802), 2.353 (2.071 - 2.827), and 2.587 (1.936 - 2.911), respectively; (2) the period effects were the lowest for the period of 2006 - 2010, with the effect values (95%CI) of - 0.497 (- 0.793 - - 0.139), - 0.234 (- 0.502 - - 0.119), and - 0.619 ( - 0.913 - - 0.205) for all, urban, and rural populations and the highest for the 2016 - 2020 period, with the effect values (95%CI) of 0.591 (0.074 - 0.629), 0.616 (0.293 - 0.956), and 0.570 (0.119 - 0.897) for all, urban, and rural populations, respectively; (3) the birth cohort effects were the highest for all, urban, and rural populations born in 1929 - 1933, with the effect values (95%CI) of 1.630 ( 0.849 - 1.979), 1.713 (1.029 - 1.938), and 1.203 (0.639 - 1.712) and were the lowest for all, urban, and rural populations born in 1999 - 2003, with the effect values (95%CI) of - 2.574 ( - 2.991 - 1.249), - 2.733 (- 3.370 - 2.238), and - 1.856 (- 2.193 - 0.329), respectively. ConclusionThe AMI mortality rate among urban and rural residents aged 15 - 79 years in China showed an increasing trend from 2006 to 2020, and the risk of AMI mortality was positively correlated with changes in age, increased with time, and decreased with successive birth cohorts during this period.